2013
DOI: 10.1007/s13187-013-0550-5
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of a Community–Academic–Clinical Partnership to Reduce Prostate Cancer Disparities in the South

Abstract: Background Engaging partners in the planning, implementation, and evaluation of cancer education programs is critical for improving the health of our communities. A two-year pilot education intervention on prostate cancer decision making and participation in medical research was funded by the National Cancer Institute. The partnership involving community members and clinical staff at a cancer center was used to develop recruitment strategies and plan for the implementation of the intervention with African-Amer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 13 publications
1
24
0
Order By: Relevance
“…Partners envisioned the SC-HBRN collaboration as a conglomeration of many different skillsets that contribute to different aspects of the overall mission of the program. These findings are consistent with other studies (Friedman et al, 2014; Zgibor et al, 2016) that demonstrated the effectiveness of using resources and strengths of a variety of organizations in order to address a larger health issue.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Partners envisioned the SC-HBRN collaboration as a conglomeration of many different skillsets that contribute to different aspects of the overall mission of the program. These findings are consistent with other studies (Friedman et al, 2014; Zgibor et al, 2016) that demonstrated the effectiveness of using resources and strengths of a variety of organizations in order to address a larger health issue.…”
Section: Discussionsupporting
confidence: 92%
“…Specifically, previous research emphasizes the importance of establishing trust and mutual respect among all entities of the network (Caldwell et al, 2015; Galea et al, 2001; Israel et al, 2001; Lantz, Virull-Fuentes, Israel, Softly, & Guzman, 2001; Maciak, Guzman, Santiago, Villalobos, & Israel, 1999; Parker et al, 2003; Schulz, Krieger, & Galea, 2002; Seifer, 2006; Seifer, Shore, & Holmes, 2003; Sullivan, Chao, Allen, Pierre-Louis, & Krieger, 2002), practicing equality of power and influence among the various partners (Friedman et al, 2014; Israel et al, 2001; Lantz et al, 2001), and producing direct benefits to members of the larger community (Israel et al, 2001; Israel et al, 1998; Maciak, Murray-Close, & Monsey, 1999; Seifer, 2006; Zgibor et al, 2016). Factors identified as challenging to the creation of a successful health-focused research network include the extensive time needed to communicate and collaborate effectively with partners (Caldwell et al, 2015; Ferman & Hill, 2004; Seifer, 2006), lack of trust among partners (Ferman & Hill, 2004; Fulbright-Anderson et al, 2001; Israel et al, 1998), and the contrasting agendas of individual organizations involved (Ferman & Hill, 2004; Israel et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…We worked with clinical and community partners to conceptualize and develop a research and recruitment plan (40, 41). Specific strategies included, but were not limited to, partnering with a prostate nurse navigator at the clinical site, multi-media promotion, and word of mouth (4043).…”
Section: Findings: Recruitment Strategies and Resultsmentioning
confidence: 99%
“…Engaging partners and potential stakeholders in cancer education programs is essential for improving community health and encouraging and supporting sustainability of such programming [16-18]. The statewide videoconference was recorded and the online link that has been shared with communities via the state cancer alliance can be used by other researchers, partners, funders, and stakeholders to continue to educate AA men and women and cancer, prostate cancer, and general prostate health.…”
Section: Discussionmentioning
confidence: 99%
“…Incorporating culturally appropriate and targeted messages and images [7-10], conducting faith-based initiatives [11, 12], and delivering educational programs in non-traditional venues such as barber shops [13] and beauty salons [14, 15] have been commonly used. Engaging partners and stakeholders in the planning, implementation, and evaluation of health and cancer education programs is critical for improving the health of our communities and for encouraging community engagement, empowerment, and capacity building [16-18]. Thus, we developed a prostate cancer IDM education program for AA families in collaboration with community and clinical partners.…”
Section: Introductionmentioning
confidence: 99%